The alogenide minerals atacamite, iodargyrite in the epithermal gold mineralization of Profitis Ilias Milos island and their importance - ΔΗΜΟΥ, Ε. (Bulletin of the Geological Society of Greece, 2001)
The present work refers to the mineralogical study of samples from borehole cores drilled in Profitis Ilias area at Milos island by the company "MIDAS" S.A., subsidiary of "Silver& Baryte Ores Mining Co" S.A., within the frames of the exploration for epithermal gold and silver. Intensely hydrothermally altered pyroclastic rocks of rhyodacitic composition occur in the area, transformed in a group of secondary minerals as alunite, jarosite, dickite, kaolinite, chrystobalite, chalcedony, adularla, quartz. Several quartz veins rich in barite and occasionally alunite traverse these rocks. The mineralization, located mainly into the quartz veins, is poor in metallic mineral proportion and consists of a few grains of hematite, pyrite, galena, chalcopyrite, bornite, chalcocine, tetraedrite, native gold, electrum, copper. Gold and silver of the order of 20ppm and 1300ppm respectively were observed in some core samples from boreholes of small depth (from 18 up to 21 m.). Initially, the exploration has been focused on the research for silver bearing minerals, taking also into consideration that high silver grades could not be explained by the restricted presence of electrum. However, the investigation proved that the high silver proportion derives from two rare silver alogenides minerals, Iodargyrite (Agi) and Chlorargyrite (AgCl), located into the cavities of the quartz veins or into fully altered-eroded voids of host rocks. These two alogenides present similar mineralogical properties and thus their identification was based mainly on the microanalyses. Moreover, Atakamite Cu2(OH)3Cl another alogenide mineral of emerald-green colour, has been found into the same samples. Its presence indicated increased grades in copper, since the metallic minerals of copper are almost absent. The presence of these alogenide minerals exclusively into cavities and the significant presence of alogene element iodine, suggest deposition, where the seawater (mixed or not with hydrothermal solutions) has played an important role. After the seawater intrusion into various formations (metamorphic basement, volcanic rocks) a high temperature are acquired, as well as enrichment in valuable metals (Au, Ag, Cu) which are deposited during its ascend in higher levels, mainly in form of alogenides. These rare alogenides display significant data on the general mineralization of the area and a different processing-recovery way of the valuable metals occurring into the epithermal mineralization.